Betarubin nano-composite liposome, preparation method and application of betarubin nano-composite liposome in preparation of antioxidant active agent
Beet elephant nanocomposite liposomes were prepared by ethanol injection method and layer-by-layer self-assembly technology, which solved the problems of beet elephant instability and liposome prone to leakage, achieved high stability and antioxidant under different conditions, and was suitable for food and medicine fields.
Patent Information
- Application Number
- CN202510681015.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-26
- Publication Date
- 2025-09-02
AI Technical Summary
During processing and storage, beet melanin instability is susceptible to factors such as temperature, water activity, light, pH and oxygen concentration, resulting in oxidation and decomposition. Liposomes are susceptible to pH, ionic strength and temperature during use, resulting in leakage of loading substances.
Beetle-erpene liposomes were prepared by ethanol injection method, and chitosan and sodium alginate were combined on the surface of the liposomes through layer-by-layer self-assembly technology to form a double-layer protective film to improve stability.
It improves the stability of beet erythrone at different pH, ionic strength and storage time, significantly enhances the antioxidant capacity, and is suitable for food and medicine fields.
Smart Images

Figure CN120570840A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of medicine and health care, and in particular relates to a betalain nanocomposite liposome, a preparation method and application thereof in the preparation of an antioxidant. Background Art
[0002] Betalain is a water-soluble natural pigment found widely in plants of the Chenopodiaceae order, primarily in beetroot and pitaya. It is formed by the cyclic condensation of betaine and 3,4-dihydroxyphenylalanine (DOPA). Betalain exhibits numerous biological functions: the phenolic hydroxyl and cyclic amine groups in its structure enable it to directly scavenge free radicals and provide antioxidant properties. Betalains also exhibit anti-inflammatory, cancer cell growth inhibition, blood pressure, lipid, and blood sugar reduction, and liver protection. Currently, betalains are highly sought after for their safety and low toxicity, and are widely used in industries such as food, pharmaceuticals, cosmetics, textiles, and chemicals. However, betalains are unstable, making them susceptible to oxidative decomposition during processing and storage due to factors such as temperature, water activity, light, pH, and the presence of oxygen and metals in the environment.
[0003] Liposomes are bilayer-enclosed vesicles composed of cholesterol and phospholipids, typically with a diameter of 50 to 500 nm. Liposomes are amphiphilic and can encapsulate both hydrophilic and hydrophobic substances. They possess the characteristics of biocompatibility, biodegradability, non-immunogenicity, low toxicity, targeting, controlled release, and long-lasting efficacy. In summary, liposomes, as a carrier, are primarily used to encapsulate functional compounds. Due to their unique structure and properties, they have broad application prospects in drug delivery, gene therapy, cosmetics, and the food industry. However, over time, liposomes are prone to aggregation, sedimentation, and fusion. During use, liposomes are also susceptible to the effects of pH, ionic strength, and temperature, leading to leakage of the loaded substances.
[0004] To improve the stability and delivery efficiency of liposomes, biopolymers can be introduced onto the liposome surface. These polymers can effectively isolate phospholipids through bilayer modification, thereby reducing the risk of liposome hydrolysis. Furthermore, the modifier polymer can form electrostatic bridges between phospholipids and polymer molecules, significantly reducing the permeability of the phospholipid bilayer and thereby improving the overall stability of the drug-loaded liposome system. Layer-by-layer self-assembly utilizes intermolecular electrostatic attraction and hydrogen bonding as driving forces to combine liposomes with modified polymers to construct monolayer, bilayer, or even multilayer protective membranes. The advantage of this approach is that it not only effectively enhances liposome stability but also fully utilizes the properties of the modified substances to achieve synergistic effects between multiple polymers. Given the current status, it is crucial to develop betalain nanocomposite liposomes to improve their stability at varying pH and ionic strengths, extend storage time, and enhance antioxidant activity. Summary of the Invention
[0005] In order to improve the stability of betalain, the present invention uses betalain from red beet as raw material and utilizes ethanol injection method and layer-by-layer self-assembly technology to develop a betalain nanocomposite liposome (Sa-Cs-Lip), which can not only improve stability and storage time, but also improve antioxidant activity and bioavailability, showing broad prospects in the fields of food, medicine and other management.
[0006] The present invention utilizes an ethanol injection method to embed betacyanin into liposomes to prepare betacyanin liposomes (Lip). Furthermore, chitosan and sodium alginate are electrostatically bound to the liposomes using layer-by-layer self-assembly technology to prepare chitosan-betacyanin composite liposomes (Cs-Lip) and sodium alginate-chitosan-betacyanin composite liposomes (Sa-Cs-Lip). DLS characterization of the composite liposomes revealed excellent stability in terms of pH, storage, salt concentration, and ion type, overcoming the limitation of betacyanin's easy degradation. In particular, the sodium alginate-chitosan-betacyanin composite liposomes (Sa-Cs-Lip) exhibited superior antioxidant properties to betacyanin.
[0007] The preparation method of the betalain nanocomposite liposomes of the present invention comprises the following steps:
[0008] (1) Extraction and purification of betacyanin:
[0009] 400-600 g of red beetroot is weighed, washed, peeled, and crushed. The resulting red beet pulp is extracted with distilled water at room temperature for 1-3 hours, filtered, and the supernatant is collected. The supernatant is added to a chromatography column filled with macroporous adsorption resin X-5 at a flow rate of 2.0-3.0 mL / min. After 2-5 hours, the column is eluted with a 20-40% ethanol solution at a flow rate of 2.0-3.0 mL / min. The collected eluate is rotary evaporated in a water bath at 40-50° C. to remove ethanol, and the column is freeze-dried into a powder to obtain a crude betalain product.
[0010] Weigh 8-10 g of Sephadex LH-20 gel, add 100-200 mL of 10% methanol solution, leave at room temperature for 4-8 hours to allow it to fully swell, then ultrasonicate for 20-40 minutes to remove bubbles, to obtain a pretreated dextran gel;
[0011] The crude betacyanin product is dissolved in a 10% by mass methanol solution, then filtered through a 0.22 μm filter membrane and sonicated to obtain a 20-120 mg / mL methanol solution of the crude betacyanin product; the pretreated dextran gel is uniformly loaded into a chromatography column while stirring, and then the crude betacyanin product methanol solution is added at a loading rate of 0.2-0.6 mL / min. After the liquid level of the crude betacyanin product methanol solution is flush with the liquid level of the dextran gel, a 10% by mass methanol solution is added for elution; the collected eluate is rotary evaporated in a water bath at 40-55° C. to remove methanol, and the powder is lyophilized to obtain a powder, which is then dissolved in water to obtain a 1.5-3.0 mg / mL betacyanin aqueous solution, thereby completing the extraction and purification of the betacyanin;
[0012] (2) Preparation of betalain liposomes (Lip): Using the ethanol injection method, 110-130 mg of lecithin and 20-30 mg of cholesterol were weighed and dissolved in 10-15 mL of anhydrous ethanol, and ultrasonically dissolved to obtain a mixed solution of lecithin and cholesterol; 5 mL of the 1.5-3.0 mg / mL betalain aqueous solution obtained in step (1) was taken, and then the mixed solution of lecithin and cholesterol was quickly injected into the betalain aqueous solution using a 1 mL syringe, and the mixture was heated at 35 °C. The mixture was stirred at a constant temperature of 40°C for 30 to 35 minutes, and then the obtained liquid was subjected to rotary evaporation in a water bath at 40 to 45°C to remove anhydrous ethanol; after ultrasonication for 2 to 5 minutes (power 100W), the obtained liquid was placed in a 7 kDa dialysis bag, and the dialysate was PBS, and the dialysate was changed every 3 to 4 hours until the dialysate was colorless; the liposome suspension obtained in the dialysis bag was filtered through a 0.22 μm filter membrane to obtain betacyanin liposomes (Lip), and unentrapped betacyanin was removed by dialysis;
[0013] (3) Preparation of chitosan-betacyanin liposomes (Cs-Lip): Weigh 0.1-0.4 g of chitosan powder, dissolve it in 50 mL of 1% (v / v) glacial acetic acid solution, and stir it thoroughly to completely dissolve it to obtain a chitosan solution; slowly add the betacyanin liposomes (Lip) obtained in step (2) to the chitosan solution at a volume ratio of 1:1, stirring while adding, and stirring at room temperature for 50-70 minutes after the addition is completed. After standing for 20-40 minutes, centrifuge at 6000-10000g for 20-40 minutes; remove the supernatant and resuspend it in distilled water to obtain chitosan-betacyanin liposomes (Cs-Lip), which are stored in a refrigerator at 4°C for use;
[0014] (4) Preparation of betalain nanocomposite liposomes (Sa-Cs-Lip): Weigh 20-50 mg of sodium alginate, dissolve it in 40-60 mL of distilled water, and stir it thoroughly to completely dissolve it to obtain a sodium alginate solution; slowly add the chitosan-betalain liposomes (Cs-Lip) obtained in step (3) to the sodium alginate solution at a volume ratio of 1:1, stirring while adding, and after the addition is completed, continue stirring for 50-70 minutes at room temperature for embedding, and after embedding, let it stand at 4°C for 10-15 hours to obtain sodium alginate-chitosan-betalain liposomes, namely the betalain nanocomposite liposomes (Sa-Cs-Lip), which are sealed and stored.
[0015] The betalain nanocomposite liposome (Sa-Cs-Lip) of the present invention is prepared by the above method.
[0016] The betalain nanocomposite liposome (Sa-Cs-Lip) described in the present invention can exhibit high stability under different pH, ion types, ionic strengths, and storage times, and can therefore be used in the preparation of antioxidants.
[0017] Compared with the prior art, the present invention has the following advantages:
[0018] (1) The betalain complex liposomes prepared by the present invention are widely available, simple to operate, require few equipment, are easy to form, and are low in cost, making them suitable for widespread preparation. Furthermore, the biopolymers bound to the liposomes are non-toxic and highly biocompatible, and thus have broad application prospects in the fields of food and medicine.
[0019] (2) The betalain complex liposomes described in the present invention exhibit high stability under different pH, ion type, ionic strength and storage time conditions, and significantly improve the antioxidant capacity of betalain, making it a potential new food additive to replace betalain;
[0020] (3) The betacyanin nanocomposite liposomes (Sa-Cs-Lip) constructed by the present invention maintain stable particle size under acidic and alkaline conditions; under different metal ion and high salt conditions, the stability of betacyanin liposomes modified with sodium alginate and chitosan is better than that of chitosan monolayer modification (Cs-Lip); the particle size of Sa-Cs-Lip changes the least with increasing storage time; the antioxidant capacity of Sa-Cs-Lip is higher than that of betacyanin, indicating that betacyanin nanocomposite liposomes greatly improve the stability, storage capacity and antioxidant activity of betacyanin. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1: These are the DLS characterization data of betalain liposomes (Lip), chitosan-betalain liposomes (Cs-Lip), and sodium alginate-chitosan-betalain liposomes (Sa-Cs-Lip) in Example 1, where (a) is a graph of particle size and dispersion coefficient, and (b) is a graph of potential;
[0022] Figure 2 1 are transmission electron micrographs of betalain liposomes (Lip), chitosan-betalain liposomes (Cs-Lip), and sodium alginate-chitosan-betalain liposomes (Sa-Cs-Lip) in Example 1, corresponding to (a), (c), and (e), respectively; wherein (b), (d), and (f) are magnified views of the local areas of (a), (c), and (e), respectively;
[0023] Figure 3 IR spectra of betacyanin liposomes (Lip), chitosan-betacyanin liposomes (Cs-Lip), sodium alginate-chitosan-betacyanin liposomes (Sa-Cs-Lip), betacyanin (Betacyanin), chitosan (Cs), and sodium alginate (Sa) in Example 1;
[0024] Figure 4 The DLS characterization data of betalain liposomes (Lip), chitosan-betalain liposomes (Cs-Lip), and sodium alginate-chitosan-betalain liposomes (Sa-Cs-Lip) at different pH values in Example 1 are shown, where (a), (b), and (c) are bar graphs of potential, particle size, and dispersion coefficient, respectively;
[0025] Figure 5 : These are the DLS characterization data of betalain liposomes (Lip), chitosan-betalain liposomes (Cs-Lip), and sodium alginate-chitosan-betalain liposomes (Sa-Cs-Lip) under different ion types in Example 1, where (a), (b), and (c) are bar graphs of potential, particle size, and dispersion coefficient, respectively;
[0026] Figure 6 The DLS characterization data of betalain liposomes (Lip), chitosan-betalain liposomes (Cs-Lip), and sodium alginate-chitosan-betalain liposomes (Sa-Cs-Lip) at different ion concentrations in Example 1 are shown, where (a), (b), and (c) are bar graphs of potential, particle size, and dispersion coefficient, respectively;
[0027] Figure 7 The particle size change curves (a) and the actual observation diagram (b) of betalain liposomes (Lip), chitosan-betalain liposomes (Cs-Lip) and sodium alginate-chitosan-betalain liposomes (Sa-Cs-Lip) at different storage times in Example 1 are shown;
[0028] Figure 8 It is a bar graph of the total antioxidant capacity of the purified betacyanin (Betacyanin), blank liposomes (Blank), betacyanin liposomes (Lip), chitosan-betacyanin liposomes (Cs-Lip), and sodium alginate-chitosan-betacyanin liposomes (Sa-Cs-Lip) in Example 1. DETAILED DESCRIPTION
[0029] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0030] Example 1
[0031] This embodiment provides a method for preparing betalain complex liposomes, and the required drugs are as follows:
[0032] Commercially available red beetroot, macroporous adsorption resin X-5, and dextran gel (Sephadex LH-20) were purchased from Shanghai Yuanye Biotechnology Co., Ltd., hydrochloric acid (HCl), sodium hydroxide (NaOH), sodium chloride (NaCl), magnesium chloride (MgCl2), calcium chloride (CaCl2), and aluminum chloride (AlCl3) were all purchased from Sinopharm Chemical Reagent Co., Ltd., lecithin, cholesterol, chitosan, and sodium alginate were all purchased from Shanghai Aladdin Reagent Co., Ltd., and the total antioxidant capacity detection kit was purchased from Shanghai Beyotime Biotechnology Co., Ltd.
[0033] The specific synthesis method is as follows:
[0034] (1) Extraction and purification of betacyanin:
[0035] 500 g of red beetroot was weighed, washed, peeled, and crushed. The resulting red beet pulp was extracted with distilled water at room temperature for 2 hours, filtered, and the supernatant was collected. The supernatant was added to a chromatography column containing macroporous adsorption resin X-5 at a flow rate of 2.5 mL / min. After 3 hours, the column was eluted with a 30% ethanol solution at a flow rate of 2.5 mL / min. The collected eluate was evaporated in a 45°C water bath to remove ethanol, and dried to a powder using a freeze dryer to obtain a crude betalain product.
[0036] Weigh 10 g of Sephadex LH-20 gel, add 150 mL of 10% methanol solution, and let it stand at room temperature for 6 hours to allow it to fully swell. Then, ultrasonicate for 30 minutes to remove bubbles to obtain the pretreated sephadex gel.
[0037] The crude betacyanin product was dissolved in a 10% by mass methanol solution, then filtered through a 0.22 μm filter membrane and sonicated to obtain a 100 mg / mL methanol solution of the crude betacyanin product; the pretreated dextran gel was uniformly loaded into a chromatography column while stirring, and then the crude betacyanin product methanol solution was added at a loading rate of 0.5 mL / min. After the liquid level of the crude betacyanin product methanol solution was flush with the liquid level of the dextran gel, a 10% by mass methanol solution was added for elution; the collected eluate was rotary evaporated in a 45°C water bath to remove methanol, and the powder was lyophilized to obtain a 2.0 mg / mL betacyanin aqueous solution, thereby completing the extraction and purification of betacyanin;
[0038] (2) Preparation of blank liposomes:
[0039] The ethanol injection method was used: 120 mg of lecithin and 30 mg of cholesterol were weighed and dissolved in 12 mL of anhydrous ethanol, and the mixture was fully dissolved by ultrasonication to obtain a mixed solution of lecithin and cholesterol. The mixed solution of lecithin and cholesterol was quickly injected into 5 mL of distilled water using a 1 mL syringe and stirred at a constant temperature of 40°C for 30 minutes. The obtained liquid was then rotary evaporated in a 40°C water bath to remove the anhydrous ethanol. The liposome suspension obtained by rotary evaporation was then filtered through a 0.22 μm filter membrane to obtain blank liposomes.
[0040] (3) Preparation of betalain liposomes (Lip):
[0041] The ethanol injection method is adopted: 120 mg of lecithin and 30 mg of cholesterol are weighed and dissolved in 12 mL of anhydrous ethanol, and the lecithin and cholesterol mixed solution is obtained by ultrasonication; the betacyanin aqueous solution (5 mL, 2.0 mg / mL) prepared in step (1) is added to a beaker, and the lecithin and cholesterol mixed solution is quickly injected into the betacyanin aqueous solution with a 1 mL syringe, and stirred at a constant temperature of 40° C. for 30 min, and then the obtained liquid is evaporated in a 40° C. water bath to remove anhydrous ethanol; after ultrasonication for 3 min (power 100 W), the obtained liquid is placed in a 7 kDa dialysis bag, and the dialysate is PBS, and the dialysate is changed every 4 hours until the dialysate is colorless; the liposome suspension obtained in the dialysis bag is filtered through a 0.22 μm filter membrane to obtain betacyanin liposomes (Lip), and the unentrapped betacyanin is removed by dialysis;
[0042] (4) Preparation of chitosan-betalain liposomes (Cs-Lip):
[0043] Weigh 0.3 g of chitosan powder and dissolve it in 50 mL of 1% (v / v) glacial acetic acid solution, stirring it thoroughly to completely dissolve it, to obtain a chitosan solution; slowly add the betacyanin liposomes (Lip) prepared in step (3) to the chitosan solution at a volume ratio of 1:1, stirring while adding, stirring at room temperature for 60 minutes after the addition is completed, letting it stand for 30 minutes, and then centrifuging it at 8000g for 30 minutes; remove the supernatant and add 25 mL of distilled water to resuspend it to obtain chitosan-betacyanin liposomes (Cs-Lip), which are stored in a 4°C refrigerator for use;
[0044] (5) Preparation of sodium alginate-chitosan-betacyanin liposomes (Sa-Cs-Lip):
[0045] Weigh 40 mg of sodium alginate, dissolve it in 50 mL of distilled water, and stir it thoroughly to completely dissolve it to obtain a sodium alginate solution; slowly add the chitosan-betacyanin liposomes (Cs-Lip) prepared in step (4) dropwise into the sodium alginate solution at a volume ratio of 1:1, stirring while adding dropwise. After the addition is completed, continue stirring at room temperature for 60 minutes for embedding. After embedding, let it stand in a refrigerator at 4°C for 12 hours to obtain sodium alginate-chitosan-betacyanin liposomes (Sa-Cs-Lip, product mass is about 55 mg), which are sealed and stored.
[0046] Example 2
[0047] In this example, the betalain nanocomposite liposome obtained in Example 1 was characterized by DLS. Figure 1 As shown in the figure, the particle size of Lip is 239.43 nm. After modification with chitosan and sodium alginate, the particle size of Cs-Lip increases to 358.81 nm, and the particle size of Sa-Cs-Lip increases to 429.90 nm. The PDI of Lip, Cs-Lip, and Sa-Cs-Lip solutions is below 0.25. The potential of Lip is -12.30 mV. After binding with chitosan, the potential of Cs-Lip turns from negative to positive, reaching 29.67 mV. After the addition of sodium alginate, the potential of Sa-Cs-Lip drops to -24.90 mV.
[0048] Example 3
[0049] In this example, the betalain nanocomposite liposomes obtained in Example 1 were characterized by transmission electron microscopy. A certain amount of Lip, Cs-Lip, and Sa-Cs-Lip solutions were dripped onto a copper grid. After air-drying, the solution was negatively stained with 1% phosphotungstic acid. After the solution was allowed to stand for 30 seconds, the excess negative stain was removed with filter paper. After air-drying, the solution was observed.
[0050] The transmission electron microscopy results in Example 1 are as follows Figure 2 As shown in the figure, all three liposomes are elliptical in shape. As can be seen from the figure, (a) and (b) are the microscopic morphology of Lip. The liposomes are spherical, with fingerprint structure characteristics visible inside, and the particle size is about 200nm. (c) and (d) are the microscopic morphology of Cs-Lip. It can be found that its morphology is still spherical, but the particle size is slightly larger than that of Lip, about 350nm, and there is a layer of material wrapped on the surface, which successfully confirms the mutual binding of chitosan and the surface of Lip. (e) and (f) are the microscopic morphology of Sa-Cs-Lip, which is also elliptical, with a particle size of about 430nm, which is larger than that of Cs-Lip. This shows that chitosan and sodium alginate wrap the liposomes layer by layer, successfully modifying the betacyanin liposomes with a double layer.
[0051] Example 4
[0052] In this example, betacyanin, Lip, Cs-Lip, Sa-Cs-Lip, chitosan and sodium alginate in Example 1 were subjected to solid infrared spectroscopy scanning. The measurement conditions are as follows: the prepared betacyanin, Lip, Cs-Lip and Sa-Cs-Lip were poured into a plate, pre-frozen at -80°C for 24 hours, and then freeze-dried into powder using a freeze dryer. With potassium bromide as the background, the freeze-dried sample was mixed with potassium bromide at a ratio of 1:100 (v / v) and tabletted. Under vacuum conditions at room temperature, the mixture was dried at 4000-400 cm -1 Scan 32 times within the range.
[0053] The experimental results are as follows Figure 3 As shown, betalain 989cm -1 The aromatic CH stretching vibration peak at 966 cm-1 is shifted to 966 cm-1 in Lip. -1 In the infrared spectrum of Lip, 1735cm -1 The peak at 1664 cm is the carbonyl C≡O stretching vibration peak in the phospholipid molecules in the liposomes. The characteristic peak of chitosan is 1664 cm -1 and 1595cm -1 , which is the NH vibration of amino group. These two characteristic peaks are not found in Cs-Lip, which proves that chitosan is successfully bound to the surface of Lip through electrostatic interaction. The structural characteristic peak of sodium alginate is at 1600cm -1 There is no obvious characteristic absorption peak of chitosan and sodium alginate in Sa-Cs-Lip, which means that the NH 3+ The -COO- link of sodium alginate successfully attached to the surface of Cs-Lip. 1097cm -1 The absorption peak at is the hydrophilic polar part of the phospholipid molecule PO2- stretching vibration, while in Cs-Lip and Sa-Cs-Lip PO 2- The characteristic absorption peak of 2922cm increases, indicating that the combination of chitosan and sodium alginate with liposomes will change most of the hydrogen bonds of the phospholipid groups on their surface. -1 and 2850cm -1 The positions of the two peaks remain unchanged in Cs-Lip and Sa-Cs-Lip, indicating that chitosan and sodium alginate undergo electrostatic cross-linking with the phosphate groups on the surface of liposomes to form hydrogen bonds.
[0054] Example 5
[0055] This example examines the stability advantages of Lip, Cs-Lip, and Sa-Cs-Lip in Example 1 by evaluating their DLS characteristics at different pH values. The pH values of Lip, Cs-Lip, and Sa-Cs-Lip were adjusted to 2, 6, and 10 using 0.1M HCl and 0.1M NaOH solutions. After standing at room temperature for 2 hours, the solutions were diluted 40-fold, 40-fold, and 20-fold, respectively. Zeta potential, average particle size, and PDI were measured at 25°C.
[0056] The experimental results are as follows Figure 4 As shown, the potential of Lip is positive at pH 2. As the pH increases, the potential changes from positive to negative, from 15.60 mV to -9.46 mV. At pH 10, the potential of Cs-Lip decreases to 5.56 mV. At pH 2, the potential of Sa-Cs-Lip changes to 11.43 mV. Under alkaline conditions, the solubility of chitosan decreases and the amino groups react with OH-, weakening the electrostatic repulsion and insufficient binding to Lip, resulting in liposome aggregation and sedimentation. The particle size increases to 595.83 nm, and the PDI increases to 0.49. The particle size of Sa-Cs-Lip is relatively stable under different pH conditions. When sodium alginate interacts electrostatically with Cs-Lip, a second protective layer is formed on its surface, making Sa-Cs-Lip more stable in extreme environments.
[0057] Example 6
[0058] In this example, the stability advantages of Lip, Cs-Lip, and Sa-Cs-Lip in Example 1 were investigated by evaluating the changes in DLS characterization values under different ion types. The measurement process was as follows: Prepare potassium chloride, magnesium chloride, calcium chloride, and aluminum chloride solutions with a concentration of 400 mM, mix them with Lip, Cs-Lip, and Sa-Cs-Lip solutions at a ratio of 1:1 (v / v), let them stand at room temperature for 2 h, then dilute the solutions 40 times, 40 times, and 20 times respectively, and measure the changes in Zeta potential, average particle size, and PDI at 25°C.
[0059] The experimental results are as Figure 5 shown. Mg 2+ and Ca 2+ will have a certain impact on the stability of Lip, Cs-Lip, and Sa-Cs-Lip. Chitosan modification significantly enhances the impact of ions on the stability of Lip, increasing the particle size to 2079.67 nm, while the double-layer modification of sodium alginate can slow down this impact and better protect the liposomes. K + has no obvious impact on Lip and Sa-Cs-Lip, but under the action of K + , the particle size of Cs-Lip will increase slightly, increasing to 444.57 nm, and the PDI is 0.40. Lip, Cs-Lip, and Sa-Cs-Lip can maintain good stability in the AlCl3 solution.
[0060] Example 7
[0061] In this example, the stability advantages of Lip, Cs-Lip, and Sa-Cs-Lip in Example 1 were investigated by evaluating the changes in DLS characterization values under different ion types. The measurement process was as follows: Prepare NaCl solutions with different concentrations (200, 400, 600, 800, and 1000 mM), mix them with Lip, Cs-Lip, and Sa-Cs-Lip solutions at a ratio of 1:1, let them stand at room temperature for 2 h, then dilute the solutions 40 times, 40 times, and 20 times respectively, and measure the changes in Zeta potential, average particle size, and PDI at 25°C.
[0062] The experimental results are as Figure 6 shown. As the ionic strength increases, the particle size of Lip will decrease, from 227.10 nm in distilled water to 183.56 nm in high-concentration solutions. The liposome structure is unstable, and the PDI increases, reaching a maximum of 0.325. The particle sizes of Cs-Lip and Sa-Cs-Lip decrease slightly with the increase in ionic concentration, and chitosan and sodium alginate bind more tightly to Lip. The relationship of particle size always remains Lip < Cs-Lip < Sa-Cs-Lip, indicating that chitosan and sodium alginate play a protective role for liposomes and betacyanin.
[0063] Example 8
[0064] In order to evaluate the stability of the betalain complex liposomes involved in the present invention during storage, the prepared Lip, Cs-Lip, and Sa-Cs-Lip samples were stored at 4°C in the dark for 28 days. The average particle size of the samples was measured at 1, 3, 5, 7, 14, 21, and 28 days, and the changes in the sample solutions were observed. The results are shown in Figure 2. Figure 7 As shown in (a), the particle size of Lip fluctuated most significantly, and a small amount of precipitation was observed in the Lip solution at 28 days. The particle size of Cs-Lip increased from 322.43 nm at the beginning to 439.56 nm at day 28. The particle size of Sa-Cs-Lip did not change significantly over time, increasing from 433.83 nm at the beginning to 449.93 nm at day 28. The Sa-Cs-Lip solution also remained unchanged. The stability of the liposomes followed a trend of Sa-Cs-Lip > Cs-Lip > Lip. Modification with chitosan increased the stability of Lip, while modification with sodium alginate increased the stability of Cs-Lip. This improved stability may be due to the electrostatic adsorption of chitosan and sodium alginate on the liposome surface, forming a protective barrier that reduces the leakage of betalains during storage. In addition, sodium alginate can reduce the fluidity of the phospholipid membrane in the liposome, slow down the aggregation of the liposome, and improve the stability of Sa-Cs-Lip during storage. Figure 7 As shown in (b), the liposome solution of Sa-Cs-Lip was uniform at 28 days without precipitation, indicating that Sa-Cs-Lip still maintained the stability of the liposome solution after storage for 28 days.
[0065] Example 9
[0066] This example further evaluated the antioxidant capacity of the betalain complex liposomes involved in Example 1.
[0067] Prepare FRAP (iron-reduced antioxidant power) working solution:
[0068] (1) Assay buffer: 2.78 g FeCl3 (ferric chloride) diluted to 50 mL with pure water;
[0069] (2) TPTZ (triphenyltetrazolium chloride) solution: 0.078 g TPTZ was diluted to 25 mL with 40 mmol / L hydrochloric acid;
[0070] TPTZ diluent: 0.364 g anhydrous sodium acetate, 3.2 mL glacial acetic acid, dilute to 200 mL with ultrapure water (pH 3.6);
[0071] The assay buffer, TPTZ solution, and TPTZ diluent were mixed at a volume ratio of 1:1:10 to obtain the FRAP (iron-reduced antioxidant power) working solution;
[0072] Prepare standard solution:
[0073] Weigh 27.8 mg of FeSO4·7H2O and dissolve it in 1 mL of distilled water to obtain a 100 mM FeSO4 solution, which was then diluted with distilled water to 0.15, 0.3, 0.6, 0.9, 1.2, and 1.5 mM.
[0074] To a 96-well plate, 180 μL of FRAP working solution and 5 μL of distilled water, standard solution, or liposomes were added. Blank wells contained distilled water, standard curve wells contained various concentrations of FeSO₄ solutions, and test wells contained betacyanin, blank liposomes, Lip, Cs-Lip, and Sa-Cs-Lip (with a consistent betacyanin content of 100 μg / mL). Each group of three replicates contained 15 test wells. After gentle mixing, the plates were incubated at 37°C for 5 minutes. A593 was measured and the absorbance values were applied to a standard curve for the total antioxidant capacity of the FeSO₄ solution. The standard curve equation for the total antioxidant capacity of the FeSO₄ solution is y = 0.2799x + 0.0727 (y = absorbance, x = FeSO₄ concentration). The total antioxidant capacity of the sample (using the concentration of the standard FeSO₄ solution to represent the total antioxidant capacity) was calculated.
[0075] The results are as follows Figure 8 As shown, the total antioxidant capacity of betalain was 0.59 mM, while that of blank liposomes was 0.78 mM. Lip, Cs-Lip, and Sa-Cs-Lip all exhibited antioxidant capacity superior to that of betalain, with total antioxidant capacities of 1.46 mM, 1.61 mM, and 2.08 mM, respectively. This indicates that betalain complex liposomes (Sa-Cs-Lip) can significantly enhance the antioxidant capacity of betalain and can therefore be used to prepare antioxidants.
Claims
1. A method for preparing betalain nanocomposite liposomes, comprising the following steps: (1) Extraction and purification of betalain: 400-600 g of red beetroot is weighed, washed, peeled, and crushed. The resulting red beet pulp is extracted with distilled water at room temperature for 1-3 hours, filtered, and the supernatant is collected. The supernatant is added to a chromatography column filled with macroporous adsorption resin X-5 at a flow rate of 2.0-3.0 mL / min. After 2-5 hours, the column is eluted with a 20-40% ethanol solution at a flow rate of 2.0-3.0 mL / min. The collected eluate is rotary evaporated in a water bath at 40-50° C. to remove ethanol, and the column is freeze-dried into a powder to obtain a crude betalain product. The crude betacyanin product is dissolved in a 10% by mass methanol solution, then filtered through a 0.22 μm filter membrane and sonicated to obtain a 20-120 mg / mL methanol solution of the crude betacyanin product; the pretreated dextran gel is uniformly loaded into a chromatography column while stirring, and then the crude betacyanin product methanol solution is added at a loading rate of 0.2-0.6 mL / min. After the liquid level of the crude betacyanin product methanol solution is flush with the liquid level of the dextran gel, a 10% by mass methanol solution is added for elution; the collected eluate is rotary evaporated in a water bath at 40-55° C. to remove methanol, and the powder is lyophilized to obtain a powder, which is then dissolved in water to obtain a 1.5-3.0 mg / mL betacyanin aqueous solution, thereby completing the extraction and purification of the betacyanin; (2) Preparation of betalain liposomes: using the ethanol injection method, 110-130 mg of lecithin and 20-30 mg of cholesterol were weighed and dissolved in 10-15 mL of anhydrous ethanol, and the mixture was fully dissolved by ultrasonication to obtain a mixed solution of lecithin and cholesterol; 5 mL of the 1.5-3.0 mg / mL betalain aqueous solution obtained in step (1) was taken, and then the mixed solution of lecithin and cholesterol was quickly injected into the betalain aqueous solution using a 1 mL syringe, and stirred at a constant temperature of 35-40° C. for 30-35 min, and then the obtained liquid was evaporated in a water bath at 40-45° C. to remove the anhydrous ethanol; after ultrasonication for 2-5 min, the obtained liquid was placed in a 7 kDa dialysis bag, and the dialysate was PBS, and the dialysate was changed every 3-4 hours until the dialysate was colorless; the liposome suspension obtained in the dialysis bag was filtered through a 0.22 μm filter membrane to obtain betalain liposomes, and the unentrapped betalain was removed by dialysis; (3) Preparation of chitosan-betacyanin liposomes: Weigh 0.1-0.4 g of chitosan powder, dissolve it in 50 mL of 1% (v / v) glacial acetic acid solution, and stir it thoroughly to completely dissolve it to obtain a chitosan solution; slowly add the betacyanin liposomes obtained in step (2) dropwise to the chitosan solution while stirring. After the addition is completed, stir at room temperature for 50-70 minutes, let it stand for 20-40 minutes, and then centrifuge at 6000-10000g for 20-40 minutes; remove the supernatant, add distilled water and resuspend it to obtain chitosan-betacyanin liposomes, and store it in a refrigerator at 4°C for use; (4) Preparation of betalain nanocomposite liposomes: Weigh 20-50 mg of sodium alginate, dissolve it in 40-60 mL of distilled water, and stir it thoroughly to completely dissolve it to obtain a sodium alginate solution; slowly add the chitosan-betalain liposomes obtained in step (3) dropwise to the sodium alginate solution while stirring. After the addition is completed, continue stirring for 50-70 minutes at room temperature for embedding. After embedding, let it stand at 4°C for 10-15 hours to obtain sodium alginate-chitosan-betalain liposomes, i.e., the betalain nanocomposite liposomes, which are sealed for storage.
2. The method for preparing betalain nanocomposite liposomes according to claim 1, wherein: In step (1), 8 to 10 g of dextran gel is weighed, 100 to 200 mL of a 10% by mass methanol solution is added, and the mixture is allowed to stand at room temperature for 4 to 8 hours to allow the mixture to fully swell, and then the mixture is ultrasonicated for 20 to 40 minutes to remove bubbles, thereby obtaining a pretreated dextran gel.
3. The method for preparing betalain nanocomposite liposomes according to claim 1, wherein: In step (3), betalain liposomes are slowly added dropwise to the chitosan solution at a volume ratio of 1:
1.
4. The method for preparing betalain nanocomposite liposomes according to claim 1, wherein: In step (4), chitosan-betacyanin liposomes are slowly added dropwise to the sodium alginate solution at a volume ratio of 1:
1.
5. A betalain nanocomposite liposome, characterized by: The method is prepared by any one of claims 1 to 4.
6. Use of the betalain nanocomposite liposome according to claim 5 in the preparation of an antioxidant.